Makna Dibalik Cover Majalah Tempo Edisi Aib Anggaran Anies - Afandi, Nur (Institut Agama Islam Negeri Kendari, 2023)
This research aims to determine the meaning behind the cover of the 11-17 November 2019 issue of Tempo magazine with the main title